Syarie Legal Profession: With Reference to Syarie Legal Profession (Federal Territories) Act 2019 - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal, 2020)
In Islam, the disputants and their legal representatives are entrusted with the obligation of upholding absolute justice and this is ordained by Allah (swt) in several verses of the Quran. Suffice at this juncture to quote one verse where Allah (swt) proclaims: 'O ye who believe! Stand out firmly for justice, as witnesses to Allah even against yourselves or your parents or your kin and - whether it be (against) rich or poor. For Allah can best protect both. Follow not the lusts (of your hearts) lest ye swerve, and if ye distort (justice) or decline to do justice, verily Allah is well-acquainted with all that ye do.'[1] Success in a trial means success in upholding justice and rendering what is right to the rightful person. A Syarie lawyer representing a disputant is entrusted with the task of assisting the judge in arriving at a just and fair decision irrespective of the outcome of the trial, even if the decision is against the interest of his client. There may be instances where a lawyer's eloquent argument may persuade the judge in making a decision in his favour although his conscience dictates that righteousness was not on his side. In such a situation, the lawyer might have only managed to do an evil act and thus, incurred sin.[2]